Quick Evaluation Study on Fourteen (14) Major Development Programmes in Rajnandgam District of Chhattisgarh State Affected by Left Wing Extremism (LWE) - Planning Commission (Planning Commission, 2011)
The Task Force on the Left Wing Extremism (LWE) held on 23.12.2009 entrusted Programme Evaluation Organization (PEO) of Planning Commission to conduct a quick evaluation study on major development programmes in 33 districts, 8 states of the country affected by LWE.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India